RESEARCH OF BIOMASS MICRO-COGENERATION SYSTEM INTEGRATION WITH A SOLAR PV PANELS IN ZERO-ENERGY FAMILY BUILDING (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
Nowadays, any economic development is based on its sustainability. On the other hand, sustainability of the economy is no longer conceivable without efficient use of resources. Climate change and environmental degradation affects everybody and have no borders. It is essential, that all countries, regardless of their existing resources, are involved in environmental matters. The European Union (EU) has taken the initiative and has seen the possibility of transforming climate change into a guiding theme for sustainability and development in the economy. The EU has developed a green policy in order to transform all economic sectors into sustainable use of resources. EU is planning to achieve climate neutralisation in all sectors of the economy by year 2050. In order to achieve this objective, only the transformation of the industrial, transport and energy sectors will not be sufficient. The activity and willingness of each individual to achieve these objectives at their own household level will be crucial. It should change habits in all sectors important for households: food, transport, waste management and decreasing energy consumption in all mentioned sectors. Solar PV panels traditionally are used to reach zero balance, but taking in to account climatic conditions and seasonable solar irradiation activity, they can operate successfully during the summer and partly during the spring and autumn season. During the heating season, the efficiency of solar PV panel systems is very low. Use of innovative micro-cogeneration equipment producing both heat and electricity is more efficient during heating season in Latvia.In this paper case study of innovative biomass Stirling engine micro-cogeneration system integration with a solar PV panels in zero-energy family building will be present.